The Relationship Between Ultra-Processed Food Consumption With Diet Quality And Over-Nutritional Status In Young Adults: Hubungan Konsumsi Makanan Olahan Ultra Proses dengan Kualitas Diet dan Status Gizi Lebih pada Usia Dewasa Muda - Setyaningsih, Aryanti; Mulyasari, Indri; Afiatna, Puji; Putri, Happy Risa (Amerta Nutrition, 2024)
Background: A transition in diet habits towards a greater intake of ultra-processed processed foods is prone to transpire during adulthood. An elevated intake of ultra-processed processed foods affected poor diet quality and elevates the risk of developing obesity. Objectives: To ascertain the correlation between the intake of ultra-processed food, the quality of one's diet, and the prevalence of overweight in young adults. Methods: The study was undertaken using a cross-sectional design. A total of 87 participants in the study were college students between the ages of 18 and 25. They were selected using a purposive sampling technique. The data was collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess ultra-processed food intake. The Diet Quality Index-International (DQI-I) was used to evaluate the total diet quality. The Body Impedance Analyzer (BIA) was employed to measure body fat percentage and identify the nutritional status. The statistical analysis employed the Mann-Whitney and ANOVA tests. Results: There are 9.1% of the participants were classified as overweight, with a diet of low quality at a level of 62.15%. Additionally, 64.4% of the participants consumed ultra-processed foods that fell inside quintile 3. The higher the intake of ultra-processed foods, the higher the total intake of energy, carbs, proteins, and fats, which affects diet quality (r=-0.480). There is a correlation between the consumption of ultra-processed processed foods and excess nutritional status (p=0.022) and low quality of the subject's diet (p=0.000). Conclusions: High levels of ultra-processed food intake is correlated with lower diet quality and overweight nutritional status.